2015
DOI: 10.1371/journal.pntd.0003423
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Urogenital Schistosomiasis with an Integrated Control Project in Sudan

Abstract: PurposeSchistosomiasis remains a major public health concern in Sudan, particularly Schistosoma haematobium infection. This study presents the disease-reduction outcomes of an integrated control program for schistosomiasis in Al Jabalain locality of White Nile State, Sudan from 2009 through 2011.MethodsThe total population of the project sites was 482,902, and the major target group for intervention among them was 78,615 primary school students. For the cross-sectional study of the prevalence, urine and stool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(77 citation statements)
references
References 21 publications
5
70
2
Order By: Relevance
“…This study is consistent previous studies in addition to school absentiesm and poor performance [3, 5, 15, 21, 22, 26–28]. Our findings revealed that epidemio-ecological factors responsible for persistent transmission dynamics included the presence/contact with the dam, traditional fisherman culture, interation between animal-human contaminated Mape dam source of water driking, favourable subtropical climate, landscape of region, residence for at least one year and 2 km surrounding villages, and no access to Praziquantel or other antihelmintic agents for the last 2 months [2, 9, 15, 18, 22, 28, 29]. …”
Section: Discussionsupporting
confidence: 93%
“…This study is consistent previous studies in addition to school absentiesm and poor performance [3, 5, 15, 21, 22, 26–28]. Our findings revealed that epidemio-ecological factors responsible for persistent transmission dynamics included the presence/contact with the dam, traditional fisherman culture, interation between animal-human contaminated Mape dam source of water driking, favourable subtropical climate, landscape of region, residence for at least one year and 2 km surrounding villages, and no access to Praziquantel or other antihelmintic agents for the last 2 months [2, 9, 15, 18, 22, 28, 29]. …”
Section: Discussionsupporting
confidence: 93%
“…The subjects were screened and medicated with praziquantel by a control program supported by the KOICA. 8 Other studies performed in other states of Sudan reported the prevalence as 1.7% in River Nile, 23.7% in southern Kordofan, 73% in Upper Nile, and 54.2% and 71% in Gezira among the schoolchildren. 9,[13][14][15][16] The studies performed surveys on the UGS prevalence by investigating schoolchildren in the age group of 10-19 years.…”
Section: Discussionmentioning
confidence: 87%
“…8 A total of 948 participants underwent both examinations, and 198 (20.9%) were US positive and 133 (14.0%) were UM positive. The Niamey working group criteria suggested by WHO are widely accepted and used for identification of UGS-related pathologic findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations